2022
DOI: 10.3390/livers2030009
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Virus Antibodies (IgG) in the Community of Rawalpindi

Abstract: Knowledge regarding the prevalence of the hepatitis E virus (HEV) in the general population can indicate public health and personal hygiene practices in a community. HEV spreads through the fecal-oral route and contaminates drinking water through sewage. Moreover, poverty also contributes to its prevalence in developing countries, including Pakistan. A cross-sectional study was conducted on 650 blood samples taken from suspected patients of HEV in the Rawalpindi cantonment area (Pakistan) from April to Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Sixy studies were found from Italy [27][28][29] and USA [30][31][32]. The third rank were India [33,34] and Brazil [35,36].From the rest studies were found from Israel [37], Iran[38], Sri Lanka [39], Pakistan [40] and Bulgaria [41].…”
Section: Discusionmentioning
confidence: 88%
“…Sixy studies were found from Italy [27][28][29] and USA [30][31][32]. The third rank were India [33,34] and Brazil [35,36].From the rest studies were found from Israel [37], Iran[38], Sri Lanka [39], Pakistan [40] and Bulgaria [41].…”
Section: Discusionmentioning
confidence: 88%
“…6 According to the World Health Organization (WHO) factsheet (2015), there have been 20 million HEV infections yearly leading to 3.3 million cases having symptoms and 60,000 deaths, an alarming figure due to viral hepatitis . 7 Over the last 10 years , the clinical and basic research on HEV pathogenesis has gone to such an extent that the European Association for the Study of the Liver (EASL) has very recently published guidelines for the management of hepatitis E. 8 The knowledge, perception and attitudes of pregnant women hold a lot of significance. Among women 80% heard about Hepatitis E, 81% known a person ever infected with viral infection, 60% don't know that this infection was caused by virus, only 46% reported that they knew that It was transmitted through contaminated food and water, 56% reported that they knew it was transmitted by blood transfusion, 54% reported that they knew it can be transmitted sexually, 45% knew that it can be transmitted from mother to fetus, 61% reported that they knew that Hepatitis E is more dangerous in pregnancy, only 26% reported that they knew it can cause hepatic failure and only 38% reported that they knew there is vaccination of Hepatitis E. Exploring the attitude of women towards Hepatitis-E showed that only 45% reported that they were at risk of getting Hepatitis-E infection, 31% were strongly agree for that fact if they use unhygienic food they will have increased risk for hepatitis E infection, 39% of the women were disagree on the fact that occasional contact with blood will not necessarily increase their risk of getting Hepatitis-E infection, 43% of the women were disagree on the fact that vaccination is unnecessary because acquiring Hepatitis-E infection is not as serious.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal preparations are made from plant extracts and are considered effective rather than a single component; the standardization process is complex. 14,37 Furthermore, activity loss may be possible due to antagonism of the active ingredients with the extract. The survival of any plant-based drug discovery needs proper standardization.…”
Section: Challenges and Successmentioning
confidence: 99%
“…Indigenous inhabitants have reported ethnobotanical applications of various plant species against various diseases, i.e., asthma, diarrhea complication, and acne. Thousands of scientifically unidentified plant species are an untapped source of natural metabolites which could have high anticancer, antimicrobial, and antiaging potential. Much attention has been paid to extracts of plants and herbs, which, due to their natural source, possess various biochemicals to inhibit cancer cells. It is generally accepted that the heritage of nutraceuticals is naturally adapted and nourished with precious natural resources, i.e., high altitude, volcanic soil, characteristic temperature, for treating metabolic and infectious diseases, but a preliminary analysis is required to scientifically justify the utility of plant extracts and preparations for the application of potentially active nutraceuticals as demonstrated in Figure . Therefore, finding the preliminary scientific justification to defend their utility as potentially or nutritionally active ingredients is crucial . Plant extracts have discrete bioactivities that have biochemical properties by involving the physiological metabolism and their ability to improve homeostasis.…”
Section: Preliminary Analysis For Nutraceuticalsmentioning
confidence: 99%